Evaluation of the psychrotrophic specific signatures for cspA gene and 16S rDNA on the phenotype of Bacillus cereus sensu strictu - Montanhini, Maike T Maziero; Neto, Roberto Montanhini; Bittencourt, Juliana Vitória M; Pinto, José Paes de Almeida Nogueira [UNESP]; Bersot, Luciano dos Santos (Wiley, 2013)
This study characterised the psychrotrophic genotypes and phenotypes behaviour of 63 strains of Bacillus cereus sensu stricto isolated from dairy products. The presence of the cspA gene signature and the 16S rDNA mesophilic and/or psychrotrophic specific signatures was evaluated. Among the strains, 25 (39.7%) had the cspA gene signature, 38 (60.3%) had both mesophilic and psychrotrophic 16S rDNA signatures, 24 (38.1%) had only mesophilic and one exhibited only psychrotrophic. No strain grew at 7 °C. The results indicate that the presence of psychrotrophic signatures for cspA gene or the 16S rDNA did not ensure a psychrotrophic behaviour on a B. cereus phenotype. © 2013 Society of Dairy Technology.
Keywords: Dairy products; Milk processing; Polymerase chain reaction; Refrigeration